2018
DOI: 10.3389/fnmol.2018.00442
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-22 Controls Aberrant Neurogenesis and Changes in Neuronal Morphology After Status Epilepticus

Abstract: Prolonged seizures (status epilepticus, SE) may drive hippocampal dysfunction and epileptogenesis, at least partly, through an elevation in neurogenesis, dysregulation of migration and aberrant dendritic arborization of newly-formed neurons. MicroRNA-22 was recently found to protect against the development of epileptic foci, but the mechanisms remain incompletely understood. Here, we investigated the contribution of microRNA-22 to SE-induced aberrant adult neurogenesis. SE was induced by intraamygdala microinj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…To the best of our knowledge, this is the rst report showing deletion of a single miRNA in a model of status epilepticus results in an altered epilepsy phenotype. The nding supports a role for miR-22 in suppressing hyper-excitability in response to an epilepsy-precipitating injury [16,26]. The accelerated and exacerbated phenotype in miR-22 -/mice matches the overall ndings from studies that used ASOs to reduce miR-22 levels in the same model [16].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…To the best of our knowledge, this is the rst report showing deletion of a single miRNA in a model of status epilepticus results in an altered epilepsy phenotype. The nding supports a role for miR-22 in suppressing hyper-excitability in response to an epilepsy-precipitating injury [16,26]. The accelerated and exacerbated phenotype in miR-22 -/mice matches the overall ndings from studies that used ASOs to reduce miR-22 levels in the same model [16].…”
Section: Discussionsupporting
confidence: 69%
“…While we did not observe differences in status epilepticus in the intraamygdala kainic acid model, miR-22-de cient mice may display altered vulnerability to other chemoconvulsants or epileptogenic injuries. Moreover, neuronal microstructure or subtle cellular dysorganisation may have been missed presently and recent work has shown that inhibiting miR-22 after status epilepticus produces changes to dendritic branching patterns in new hippocampal neurons [26]. Finally, a limit of the present study is that we did not perform a recovery experiment.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While we did not observe differences in status epilepticus in the intraamygdala kainic acid model, miR-22-deficient mice may display altered vulnerability to other chemoconvulsants or epileptogenic injuries. Moreover, neuronal microstructure or subtle cellular dysorganisation may have been missed presently and recent work has shown that inhibiting miR-22 after status epilepticus produces changes to dendritic branching patterns in hippocampal neurons [25]. Finally, it would be interesting to determine if the knockout phenotype we observed can be recovered or obviated by the reintroduction of miR-22, for example by delivery of a mimic [16,36].…”
Section: Discussionmentioning
confidence: 99%
“…miR-9 also facilitates influenza A infection in A549 cells 36 . miR-22 is shown to control adult neurogenesis, neuronal migration and dendritic arborization 37 . It is also considered as a serum biomarker for hepatitis B infection 38 .…”
Section: Discussionmentioning
confidence: 99%